Occurrence of pests in weeds with different crop managements (Research, Society and Development, 2020)
Weeds can be important hosts for potential crop pests. Thus, the objective was to evaluate the occurrence of pests in weeds in three crop management strategies. The experiment was conducted in the 2016/17 harvest. Each management had an area of 0.5 ha, used to assess pests: (1) cotton / soybean / Urochloa decumbens; (2) millet / soybean / millet and (3) millet / soybean / Crotalaria. Pest surveys were carried out monthly on weeds during the management of soybean crops and on coverages in succession. Shannow-Weaner diversity, abundance, dominance, frequency and constancy indices and population fluctuation were determined. Fourteen species of pests were identified in association with weeds in the three rotation systems. The order Hemiptera had the largest number of individuals collected, followed by the order Lepidoptera. The millet / soybean / Crotalaria rotation provided the highest number of pests and the cotton / soybean / U. decumbens rotation had the lowest number of pests. The pests Bemisia tabaci, Aphys gossypii and Daubulus maidis presented the largest number of individuals in the evaluations in the three managements.